Simple Area Coverage by a Dynamic Set of Unmanned Aerial Vehicles - Pellegrino, Grazieno; Mota, Gustavo; Assis, Flávio; Gorender, Sérgio; Sá, Alirio (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2020: Anais do X Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2020)
The coordination of cooperating Unmanned Aerial Vehicles (UAVs) has become an active area of research. The approaches to coordinate these so-called swarms generally include a solution to a class of problems called Area Coverage as a building block. Area coverage problems consist in obtaining information about a certain interest area (commonly a polygon or a polyhedron) using a set of UAVs, generally with decentralized coordination and minimal human intervention. This problem models the requirements of different types of applications, such as in the case of emergencies and disasters, gas leak detection, seeking lost people, among many others. In this paper we describe a specific strategy to coordinate dynamic sets of UAVs to solve a specific area coverage problem. Existing solutions to the problem typically consider a fixed set of UAVs. In dynamic sets, UAVs might enter or leave the set. Beyond describing a specific strategy to the problem, we introduce the framework we are building on top of ROS/Gazebo to implement it. This framework eases the implementation of different strategies for multiple UAVs coordination and the assessment of their quality.